PENGGUNAAN MAJAS DALAM PUISI SISWA KELAS VIII SMP NEGERI 3 KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Ermayenti, Ermayenti (BAHASTRA, 2017)
This research has purpose to get description about use of majas in poetry of student of class VIII SMP Negeri 3 Koto XI Tarusan. This research is type of qualitative research using content analysis method. The data in this study is a collection of poems written by students of class VIII SMP Negeri 3 Koto XI Tarusan, while the focus of research is the utilization of the majas contained in the poem. Data collection is done by inventorying all poems written by students. Furthermore, the data were analyzed according to the content analysis method and studied based on the theory of the masters used. Based on the results of the discussion can be concluded that the majas used in the students poetry among them; (1) Parable, (2) hyperbole, (3) repetition, (4) personification, (5) metaphors, (6) ellipsis, and (7) allegory. Majus found in total amounted to 73 majas. For the dominant masters used in student poems the personification majas, amounting to 25 types of usage of 73 types of the found masters.